A Poly(cobaloxime)/Carbon Nanotube Electrode: Freestanding Buckypaper with Polymer‐Enhanced H2‐Evolution Performance. Issue 12 (18th February 2016) - Reuillard, Bertrand; Warnan, Julien; Leung, Jane J.; Wakerley, David W.; Reisner, Erwin
Abstract: A freestanding H2 ‐evolution electrode consisting of a copolymer‐embedded cobaloxime integrated into a multiwall carbon nanotube matrix by π–π interactions is reported. This electrode is straightforward to assemble and displays high activity towards hydrogen evolution in near‐neutral pH solution under inert and aerobic conditions, with a cobalt‐based turnover number (TONCo ) of up to 420. An analogous electrode with a monomeric cobaloxime showed less activity with a TONCo of only 80. These results suggest that, in addition to the high surface area of the porous network of the buckypaper, the polymeric scaffold provides a stabilizing environment to the catalyst, leading to further enhancement in catalytic performance. We have therefore established that the use of a multifunctional copolymeric architecture is a viable strategy to enhance the performance of molecular electrocatalysts. Abstract : Giving it some gas : Hybrid carbon‐nanotube‐based electrodes can be constructed in a straightforward manner by the integration of a cobaloxime‐containing copolymeric structure into a multiwall carbon nanotube matrix. The use of the cobaloxime‐containing copolymer led to a significant improvement in the electrocatalytic hydrogen‐evolution performance compared to the use of a monomeric cobaloxime (see figure).